Simplifying observation of hydrogen trapping in atom probe tomography - Chen, Y; Haley, D; Bagot, P; Moody, M (Cambridge University Press, 2017)
The presence of hydrogen within the microstructure of an alloy can lead to a serious reduction of ductility known as hydrogen embrittlement. Although the exact mechanisms of this phenomenon are still subject to debate, some mitigation strategies are available. Such strategies include minimizing hydrogen ingress with surface coatings, or controlling hydrogen diffusion within via the introduction of microstructural ‘traps’, e.g. second phase precipitates. One system of interest in ferritic steels is a microstructure containing finely distributed nano-sized vanadium carbide precipitates (~10nm M4C3), which show good resistance to hydrogen environments. However, to date, there is a lack of experimental techniques to directly study the interaction between hydrogen and microstructural features, limiting researchers’ ability to design effective microstructural hydrogen traps.